Subjective Experiences of Driving Cessation and Dementia: A Meta-Synthesis of Qualitative Literature. Issue 2 (3rd March 2020) - Sanford, Sarah; Naglie, Gary; Cameron, Duncan H.; Rapoport, Mark J.; ,
ABSTRACT: Objectives : To review qualitative research on the specific challenges and strategies that relate to driving cessation for older adults with dementia, from the perspectives of key informant groups. Method : A meta-synthesis of qualitative studies was conducted. Structured inclusion criteria were applied to screen 616 titles and abstracts, and 9 qualitative studies were included, published from 2002 to 2016. Descriptive themes were identified using content analysis and synthesized to generate analytic themes. Results : The study samples and methodologies represented a diverse range. Cross-cutting themes on experiences of driving cessation for people with dementia are the: importance of open communication and autonomy in decision-making, and advanced planning to connect people with resources; significance of relationships; importance of providing support for the impact of cessation on identity and emotional wellbeing; and benefit of individualizing supportive approaches. Conclusion : This review identifies some important areas for consideration when designing supportive programs to address driving. Clinical Implications : Interventions to support driving cessation for people with dementia should prioritize support for communication, advanced planning, and emotional effects of stopping driving.